Assessment of Endothelial Dysfunction in Childhood Obesity and Clinical Use. (3rd April 2013) - Bruyndonckx, Luc; Hoymans, Vicky Y.; Van Craenenbroeck, Amaryllis H.; Vissers, Dirk K.; Vrints, Christiaan J.; Ramet, José; Conraads, Viviane M.
Abstract : The association of obesity with noncommunicable diseases, such as cardiovascular complications and diabetes, is considered a major threat to the management of health care worldwide. Epidemiological findings show that childhood obesity is rapidly rising in Western society, as well as in developing countries. This pandemic is not without consequences and can affect the risk of future cardiovascular disease in these children. Childhood obesity is associated with endothelial dysfunction, the first yet still reversible step towards atherosclerosis. Advanced research techniques have added further insight on how childhood obesity and associated comorbidities lead to endothelial dysfunction. Techniques used to measure endothelial function were further brought to perfection, and novel biomarkers, including endothelial progenitor cells, were discovered. The aim of this paper is to provide a critical overview on both in vivo as well as in vitro markers for endothelial integrity. Additionally, an in-depth description of the mechanisms that disrupt the delicate balance between endothelial damage and repair will be given. Finally, the effects of lifestyle interventions and pharmacotherapy on endothelial dysfunction will be reviewed.